Pelatihan Manajemen Keuangan bagi Santri Dayah Darul Huda Menuju Kemandirian - Wiriani, Erni; Puspita, Esti Alemia; Evawani, Cut; Fitriani (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
Dayah is one of the Islamic Education Institutions in Aceh as a non-governmental religious non-profit organization that provides services to children of trade. Management of Financial Management is still very simple which is a resource that directly supports effectiveness, efficiency and professionalism in the management of an Islamic educational institution (Dayah). Dayah's independence is one of the priority programs of the Ministry of Religion of the Republic of Indonesia in 2022. This will be achieved by improving the quality of Dayah's management/management of financial administration that is effective, efficient, transparent, accountable and professional. PKM Financial Management Training for Santri towards Dayah independence using Participatory Action Research (PAR). That is, all interested parties (stakeholders) are actively reviewing current actions to make changes and improvements for the better. The results of community service that have been carried out are several stages of Dayah's financial management that must be carried out, namely planning (budgeting), implementation (Actuating) and evaluation (Auditing). In addition to the Dayah Management Santri, they also receive assistance in the preparation of the 2022 RKAD (Dayah Budget Activity Plan). It is hoped that Dayah's financial management will be more transparent and accountable.